Gambaran Karakteristik Rheumatoid Arthritis pada Lansia di Desa Pulau Birandang Puskesmas Kampa - Fadrus, Sri Rahmayuni; Syarif Hamidi, M. Nizar; Syahda, Syukrianti (Evidence Midwifery Journal, 2023)
The number of patients with rheumatoid arthritis in the elderly has increased. At present, between 0.5-1% of people with rheumatoid arthritis in the world are residents of Indonesia. In Kampar Regency, the incidence of rheumatoid arthritis in 2021 was 11,726 people, where the highest incidence of rheumatoid arthritis was in the UPT Puskesmas Kampa Work Area, namely 1,038 people. The purpose of this study was to describe the characteristics of rheumatoid arthritis in the elderly in Pulau Birandang Village, the Working Area of UPT Puskesmas Kampa. The research design used was descriptive with the population and sample in this study were 60 elderly people with rheumatoid arthritis using the Non Probability Sample technique. Data collection tool is a questionnaire. The results showed that the majority of elderly rheumatoid arthritis sufferers were female, as many as 40 people (66.7%), who did not have a family history of rheumatoid arthritis as many as 34 people (56.7%) and all male respondents, as many as 20 people (33.3%) ) had a smoking habit. It is hoped that the Kampa Health Center will be able to hold counseling about rheumatoid arthritis and its treatment